'As If' There Were a 'Jew': The (non)Existence of Deconstructive Responsibility. Issue 1 (May 2014) - Gaon, Stella
<x xml:space="preserve">Abstract</x> The argument of this paper hinges on Derrida's relation to Judaism as a religious heritage and/or as an essential experience. If he can be said to 'appropriate his Jewish roots' at all, as Colby Dickinson (2011) has recently proposed, this is not because Derrida concurs that all belief in an ultimate reality ('as such') must now be understood in merely conditional terms ('as if'). Rather, it is because Derrida deconstructs the difference between the Jew and the non-Jew, along with the differences between the 'as if' and the 'as such' and the performative and the constative, in his very demonstration of the impossibility of 'being-jewish'. Dickinson thus misunderstands the way in which Derrida appropriates Kant's regulative 'as if', and thus misrepresents what is at stake in Derrida's 'faith' in 'Jewishness'. What is at stake is what Derrida calls deconstructive responsibility, and it takes the form of a radical fidelity to the principle of reason (to an 'unconditional theoreticism'). This responsibility, paradoxically, demands and impels the interrogation of critical thinking itself, with its principles, its essences and its identities. Accordingly, Derrida interrupts both the 'as such' and the 'as if' with the 'if' of a dangerous 'perhaps'.